AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE SONG LYRICS OF NADIN AMIZAH - Liens Mariyanti Gowasa; Opirman Waruwu (Research on English Language Education, 2025)
This study aims to identify and analyze the types of figurative language found in four song lyrics by Nadin Amizah, namely "Beranjak Dewasa," "Kanyah," "Taru," and "Cermin." The study employs a qualitative descriptive method, with the song lyrics serving as the primary source of data. The analysis identifies seven types of figurative language used across the four songs, including simile, metaphor, personification, paradox, hyperbole, repetition, and symbolism. The findings reveal that Nadin Amizah consistently employs figurative language not merely as a stylistic device, but as the primary means of conveying deeply personal and emotional themes. Each song explores a distinct yet interconnected aspect of human experience, ranging from the pain of growing up, unconditional love, fear of romantic relationships, to the silent struggle of performing strength for others. The study concludes that Nadin Amizah's lyrics possess significant literary depth and merit serious academic attention.